2005
DOI: 10.1073/pnas.0408696102
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial glycolipids and analogs as antigens for CD1d-restricted NKT cells

Abstract: The CD1 family of proteins binds self and foreign glycolipids for presentation to CD1-restricted T cells. To identify previously uncharacterized active CD1 ligands, especially those of microbial origin, numerous glycolipids were synthesized and tested for their ability to stimulate mouse and human natural killer T (NKT) cells. They included analogs of the well known NKT cell agonist ␣-galactosyl ceramide (␣-GalCer), bacterial glycolipids, and variations of the self-glycolipid, sulfatide. Bacterial glycolipids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
190
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(195 citation statements)
references
References 33 publications
5
190
0
Order By: Relevance
“…Although Wu et al [25] had used synthetic a-GlcUCer to show that it is a CD1d-restricted antigen for NKT cells, this is in support of our results using natural a-GlcUCer extracted from S. paucimobilis. GSL-4A by itself did not stimulate NKT cell cytokine production any more than vehicle treatment and therefore served as a proper control for the bacterial-derived a-GlcUCer.…”
Section: A-glcucer Is the Nkt Cell Activating Ligandsupporting
confidence: 90%
See 2 more Smart Citations
“…Although Wu et al [25] had used synthetic a-GlcUCer to show that it is a CD1d-restricted antigen for NKT cells, this is in support of our results using natural a-GlcUCer extracted from S. paucimobilis. GSL-4A by itself did not stimulate NKT cell cytokine production any more than vehicle treatment and therefore served as a proper control for the bacterial-derived a-GlcUCer.…”
Section: A-glcucer Is the Nkt Cell Activating Ligandsupporting
confidence: 90%
“…During the preparation of this manuscript, Wu et al [25] reported that glycolipids from a related species (S. wittichii) can activate human and mouse NKT cells. Although Wu et al [25] had used synthetic a-GlcUCer to show that it is a CD1d-restricted antigen for NKT cells, this is in support of our results using natural a-GlcUCer extracted from S. paucimobilis.…”
Section: A-glcucer Is the Nkt Cell Activating Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp. [28], a-galactosyldiacylglycerol from Borrelia sp.…”
Section: Introductionmentioning
confidence: 99%
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp.[28], a-galactosyldiacylglycerol from Borrelia sp.[30], phosphatidylinositol mannoside from Mycobacterium sp.[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34].…”
mentioning
confidence: 99%